KEBERKESANAN PENGGUNAAN PETAK SIFIR DALAM PENGUASAAN FAKTA ASAS DARAB DALAM MATEMATIK TAHUN 2 - Ahad, Rosnee; Mustafa, Mohamad Zaid; Supiyan, Salina; Abdul Razzaq, Abdul Rasid (Online Journal for TVET Practitioners, 2018)
Multiplication or multiple operations is one of the basic Mathematics skills. This skill needs to be mastered at primary level so as not to make it difficult for mathematics to be at higher levels.This study aims to look at the effectiveness of the Sifir tables is compared to the traditional plot in the process of learning basic multiplication facts for Mathematics Year 2.This research was conducted to examine twenty two students of Year 2 Nilam to master the multiplication of basic facts by using the sifir table method.Students from Year 2 Nilam get a simple results in the last exams. This class has fourteen male students and eight female students.The data were collected through observation and analysis of questionnaire documents.Pre test was conducted to identify the student weaknesses in basic multiplication facts.Then the post test will be used to determine the level of student progress in multiplying skills using the sifir tablemethod.Both test is done to see an increase in achievement between twenty two students.The result of this study showed that from the pre test analysis found that 41% of the students had failed and only 59% of the students mastered during the test.After a post test, 100% of the student were mastered, where grade A sixteen (73%), grade B four (18%) and grade C two (9%).The results of this study are expected to help students master the multiplication operation by using sifir table method.